Temperature–Mediated Transition From Dyakonov Surface Waves to Surface–Plasmon–Polariton Waves - Tom G. Mackay; Akhlesh Lakhtakia (IEEE Photonics Journal, 2016)
The propagation of electromagnetic surface waves, guided by the planar interface of a temperature-sensitive isotropic material and a temperature-insensitive uniaxial material, each characterized by a relative permittivity dyadic, was investigated theoretically for the case of the optic axis of the uniaxial partnering material lying wholly in the interface plane. On raising the temperature, the isotropic partnering material (namely, InSb) transforms from a weakly dissipative dielectric material to a metal in the terahertz frequency regime. Correspondingly, the surface waves change from being Dyakonov surface waves to being surface–plasmon–polariton (SPP) waves. Numerical studies revealed that modest changes in temperature could result in dramatic changes in the numbers of propagating surface waves, their angular existence domains, their propagation constants, and their decay constants. Whereas multiple Dyakonov surface waves may propagate in a specific direction if at least one of the two partnering materials is dissipative, at most one SPP wave can propagate in a specific direction.